Problem-Based Learning Flipbook E-Module in Improving Students’ Critical Thinking Skills in "Always Save Energy" Thematic Learning - Sri Adhi Endaryati; St. Y. Slamet; Kartika Chrysti Suryandari (International Journal of Elementary Education, 2023)
The threat of the world energy crisis is a topic of discussion that needs to be emphasized in classroom learning. In addition, the integration of technology becomes one of the things that must be connected to the demands of 21st-century learning. This study aims to analyze the use of problem-based learning flipbook e-modules in thematic learning "Always Save Energy". This research is a quasi-experimental research with a pretest-posttest control group design that tests the effectiveness of the e-module in improving critical thinking skills in thematic learning "Always Save Energy". This research was conducted on fourth-grade elementary school students who were taken by purposive sampling and came from four different schools. The control group came from 1 school, namely 31 students, and the experimental group consisted of 3 schools, totalling 70 students. Test techniques become primary data collection data, while observations and interviews become research-supporting data. The data analysis technique was carried out by testing the independent sample t-test. The results showed that the flipbook e-module based on problem-based learning greatly impacted the critical thinking skills of fourth-grade elementary school students. The features presented in the electronic module make students enthusiastic about participating in the learning process to form a positive learning attitude in problem-solving.